Reduce bladder cancer recurrence in patients treated for upper urinary tract urothelial carcinoma: The REBACARE-trial - van Doeveren, T. (Contemp Clin Trials Commun, 2018)
BACKGROUND: Following radical nephro-ureterectomy for urothelial carcinoma of the upper urinary tract (UUT), the reported bladder recurrence rate of urothelial carcinoma is 22–47%. A single intravesical instillation of chemotherapy within 10 days following nephro-ureterectomy has the potential to decrease the risk of a bladder recurrence significantly. Despite recommendation by the European Association of Urology guideline to administer a single instillation postoperatively, the compliance rate is low because the risk of extravasation of chemotherapy. AIM: To reduce the risk of bladder cancer recurrence by a single intravesical instillation of Mitomycin immediately (within 3 h) before radical nephro-ureterectomy or partial ureterectomy. METHODS: Adult patients (age ≥ 18 years) with a (suspicion of a) urothelial carcinoma of the UUT undergoing radical nephro-ureterectomy or partial ureterectomy will be eligible and will receive a single intravesical instillation of Mitomycin within 3 h before surgery. In total, 170 patients will be included in this prospective, observational study. Follow-up will be according to current guidelines. RESULTS: The primary endpoint is the bladder cancer recurrence rate up to two years after surgery. Secondary endpoints are: a) the compliance rate; b) oncological outcome; c) possible side-effects; d) the quality of life; e) the calculation of costs of a single neoadjuvant instillation with Mitomycin and f) molecular characterization of UUT tumors and intravesical recurrences. CONCLUSIONS: A single intravesical instillation of Mitomycin before radical nephro-ureterectomy or partial ureterectomy may reduce the risk of a bladder recurrence in patients treated for UUT urothelial carcinoma and will circumvent the disadvantages of current therapy.